Evaluation of mobilization in operated case of fracture tibia - Jain, Ravi Kant; Varun, Ajay; Mahajan, Pranav; Deshpande, Mandar (International Journal of Research in Orthopaedics, 2018)
Background: In spite of all the advances optimal method of treatment, fractures of the tibia still pose a challenge to the orthopaedic surgeons and thus the management of the fractured tibia requires the widest experience, the greatest wisdom, and the nicest of the clinical judgement in order to choose the most appropriate treatment for particular pattern of injury. Therefore, in this study we evaluated the role of mobilization efficacy and results of nailing and plating compression in management of tibial fractures and its VAS scoring. Methods: This is a prospective study of fractures tibia in 150 cases aged from 18-60 years, out of which 109 (72.6%) were males. The left side was involved in 85(56.6%) patients and RTA was the major cause of the tibial fractures 98 (65.3%). Among the patients full weight bearing time was early (<3 weeks) with 90 (60%) and 60 (40%) patients within delay (>3 weeks) of surgery. Results: VAS score was significant better in early (<3 weeks) mobilization and in nailing treatment of tibial fractures in first month (7.8±074 and 7.6±0.81) and (2.1±0.8 and 1.8±0.65) at the final follow-up. Vas score correlation was significant with process and mobilization. Conclusions: We here conclude from our study that interlocking nailing appears to be promising method of treatment of unstable tibia fractures in adults without any external splintage after adequate stabilization and early weight bearing leading to excellent functional results in most of cases.